“Los trastornos adaptativos en el comportamiento de los estudiantes hijos de migrantes del segundo año de bachillerato de la sección vespertina de la Unidad Educativa Carlos Cisneros, año lectivo 2014-2015” - Ricaurte Jiménez, Froilán (2016)
The research paper entitled "ADAPTIVE BEHAVIORAL DISORDERS IN CHILDREN OF IMMIGRANTS FROM CARLOS CISNEROS HIGH SCHOOL ELEVEN GRADE, DURING THE 2014-2015 SCHOOL YEAR" has its origin in the migration of parents and the new responsibilities that have had been assumed by the teenagers in dysfunctional homes, or in new that are integrated by relatives or non-relative individuals. The aim of the study was to determine the incidence of adaptive behavior disorders in these children. The importance lies in providing a study framework and starting point on different approaches related to psychoeducational intervention between family and Educational Institution which seeks greater coherence and effectiveness in the intervention to the problems. The research used the hypothetical-deductive method. The methodology was quasi-experimental and the population were children of parents who have migrated belonging to Carlos Cisneros High School. The techniques were the observation, and the instrument was the survey with registration forms and questionnaires which allowed them to collect data for compliance pu rposes. The hypothesis states that the design and application of a psycho - pedagogical guide called "ADAPTÁNDOME AL CAMBIO" improves student’s performance. The z value of the normal distribution was used to test the hypothesis. The main conclusion states that the design and application of psychoeducational intervention guide improves the behavior of children whose parents are immigrants and do not reside in the country. Different reference guides, courses and workshops aimed at teachers, relatives and students were used.